Knowing, becoming, doing as teacher educators identity, intimate scholarship, inquiry - Hamilton, Mary Lynn; Pinnegar, Stefinee E. (Advances in research on teaching, 2015)
The Advances in research on teaching series was established to provide state-of-the-art conceptualization and analysis of the processes involved in functioning as a classroom teacher. These include not only the behaviors of teachers that can be observed in the classroom, but also the planning, thinking, and decision making that occur before, during, and after interaction with students.